Asset Analysis and Sustainable Strategies for Forest Management: a Case Study of the Organic Forest Farmer Group and the Citarum Watershed Upstream Farmer Group - Kurniawati Kurniawati; Kliko Teguh Budi Mulyono (International Journal Labs, 2023)
Forestry is one of the sectors that is of concern to the government, especially in management methods that are still not good so that many passive and poorly managed lands are found. Management becomes increasingly uncontrolled when the land area is very large and controlled by individuals and the government. The Hutani Farmer group or an organization that cares about the destruction of forest land can be a group that can play a local role in maintaining forest land more optimally in its management. This study aims to analyze forest assets that are a source of income in forest areas, strategies and stages of the forest asset management process, analyze product products that are output in asset management, analyze environmental and economic quality improvements on the impact of asset management and analyze environmental management related to support for the Sustainable Development Goals (SDG's). The object of research is on the management of organic forest land in megamendung and the Citarum watershed forest area in Bandung, with qualitative research methods analyzed using content analysis. Data collection was obtained from interviews of resource persons in this case forest land managers and questionnaire results as well as processed data from internal reports of the management. The results showed that forest land management requires existing forest assets in the form of trees and land as well as the existence of competent Human Resources. The main assets owned are also processed through strategies and stages in the form of agroforesty strategies and cultivation stages in the form of land zoning so as to produce outputs / products in the form of wood and non-timber which have an impact on creating better forest land for ecology, both land improvement and air quality from the results of planting existing tree species, another impact is the addition of economy for the actors in the form of vegetables and fruits and product yields. wood from several trees that can be randomly harvested. This sustainable asset management contributes to the Sustainable Development Goals (SDG's), especially in the Environment pillar and the Economic Pillar. Suggestions and implications in general so that farmer groups can maximize their HR assets to be able to form strong governance, further research can be carried out on other forest farmer groups, conduct research on downstream activities that are greater than each output produced.